Chronically Pre-treatment of Pistachio Alters the Morphology of CA1 Hippocampus Neurons Following Transient Focal Cerebral Ischemia in Male Wistar Rats - Pourmobini, Hossein; Afarinesh, Mohammad Reza; Shamsara, Ali; Eftekhar-Vaghefi, Seyed Hasan; Asadi-Shekaari, Majid (Acta Biomedica Atenei Parmensis, 2022)
Background: Consumption of antioxidants is effective on reducing the damage caused by cerebral ischemia. Objectives: We investigated the effect of Pistacia vera (pistachio) pretreatment on the morphology of the cornu ammonis (CA1) region of hippocampus neurons of the rats’ hippocampus following transient focal cerebral occlusion of the middle cerebral artery (MCA). Methods: In this study, 30 male Wistar rats were divided into 3 groups of control, ischemia, and pretreatment with pistachio (fed with pistachio at 6% of the diet for a five-week duration before the right MCA occlusion). Neurological scores of the rats were assessed using Baderson rating. Thereafter, the animals’ balance and muscle power were assessed by Rotarod and forelimb wire-grip strength tests, respectively. Finally, histopathological and morphometrical characteristics of hippocampal neurons were studied using Hematoxylin-Eosin method. Results: Neurological scores of the ischemia group significantly decreased compared to the control group (p<0.05), while pretreatment with pistachio significantly improved Baderson rating scores compared to the ischemia group (p<0.05). Although stroke significantly decreased the balance and muscular strength in the studied rats compared to the normal rats (p<0.05), pistachio’s exposure significantly increased the balance and muscular strength compared to the ischemia group (p<0.05). Additionally, a significant decrease was observed in the volume of stroke and neuronal degradation in the pistachio-treated rats compared with the ischemia group (p<0.05). Conclusions: Pistachio consumption reduces the volume of infarction and neuronal damage and improves neurological disorders after ischemia. Therefore, pretreatment with pistachio would have a protective effect against stroke.